Evaluation of locally available feeds on performance of Vanaraja birds under Kargil condition - Mondal, G; Kakati, B K; Das, T K; Mehdi, Mohd (The Indian Journal of Animal Sciences, 2012)
The present study was undertaken to evaluate the locally available feeds in Kargil on the performance of Vanaraja birds. Vanaraja birds (180) were reared from fifth weeks to 75th weeks of age with 2 feeding regimen (groups 1, 2) having 90 birds in each group (6 male, 84 female). Both the groups were fed either compound feed with maize and fishmeal or locally available feeds (wheat, barley and detoxified oilcake) for the whole experimental period. Weight gain at the end of the experiment was 2955.2 and 2903.5 g, respectively, in the 2 groups. Age at first egg laying was at 23–24 weeks in both the groups. Egg production, egg weight, shell weight, shell thickness and mortality were statistically similar in both the groups. Dressing percentage was around 71 in both the groups whereas the blood loss and feather loss was around 4.0 and 7.0%, respectively. Weight of various cuts, viz. leg, back, neck, breast and skin (% of dressed weight) was around 34, 14, 8, 23 and 19%, respectively, in both the groups. Weight of liver, gizzard, intestine, spleen and bursa was also statistically similar in both the groups. It was concluded from the present experiment that locally available feeds may be used for desired growth and egg laying performance without affecting the slaughter traits in Vanaraja birds under Kargil condition.